2020
DOI: 10.3390/nu12061549
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Impacts of Confinement during the COVID-19 Pandemic Due to Modified Diet and Physical Activity Habits

Abstract: While the detrimental effects of a chronic positive energy balance due to a sedentary lifestyle have been well established, the impacts of a short period of abruptly reduced physical activity and overeating arising from strict confinement due to the COVID-19 pandemic will soon start to emerge. To reasonably anticipate major consequences according to the available evidence, we hereby review the literature for studies that have explored the health impacts of several weeks of a reduction in physical activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
300
2
33

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(375 citation statements)
references
References 69 publications
9
300
2
33
Order By: Relevance
“…It should be noted that obesity was one of the most serious global problems defined as pandemic [26] before COVID-19 pandemic. Reduce in PA leads to muscle mass reduction in a few days [27], and as metabolic consequences of a prolonged sedentary lifestyle, increased body weight, including fat mass, and impairment of glycemic control are noted in healthy adults [11,28]. In overweight adults and in the elderly, the consequences are greater, which include lipid profile disturbance and increased inflammation and cardiometabolic risk [11].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that obesity was one of the most serious global problems defined as pandemic [26] before COVID-19 pandemic. Reduce in PA leads to muscle mass reduction in a few days [27], and as metabolic consequences of a prolonged sedentary lifestyle, increased body weight, including fat mass, and impairment of glycemic control are noted in healthy adults [11,28]. In overweight adults and in the elderly, the consequences are greater, which include lipid profile disturbance and increased inflammation and cardiometabolic risk [11].…”
Section: Discussionmentioning
confidence: 99%
“…The resultant confinement of people to their homes led to lifestyle changes, including in diet, sleep, and physical activity. Such changes have negative implications on metabolic health [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies explored the health impacts of a prolonged reduction in physical activity and overeating under circumstances of home confinement and found that increased total body fat and elevated levels of inflammatory cytokines appear to be major factors in exacerbation of insulin resistance ( 1 ). Another unhealthy consequence of COVID-19 imposed home confinement is the limited exposure to daily light, which can lead to decreased levels of Vitamin D, essential to perturb viral cellular infection by interacting with ACE2 cell entry receptors ( 37 ).…”
Section: Physical Activity and Covid-19mentioning
confidence: 99%
“…As we have just approached the 10 millionth case of the novel coronavirus disease (COVID-19) worldwide, an increasing amount of evidence has been accumulating to indicate its poorer prognosis in patients with diabetes and hypertension, who appear to be exposed to the greater risk of the severe morbidity and mortality ( 1 3 ). A recent meta-analysis demonstrated that the incidences of diabetes and hypertension were about two-fold higher, and cardio- and cerebrovascular diseases were three-fold higher in severe/intensive care unit (ICU) cases as compared to non-ICU severe cases ( 4 ).…”
Section: Introductionmentioning
confidence: 99%